How often do patients attend general practice, how often are they referred to hospital, and how do multi-morbidity and polypharmacy affect general practice attendance and referral rates? - Andrew O’Regan; Liam Glynn; Vikram Niranjamn; Raymond O'Connor; Ailish Hannigan (James Cook University, 2023)
Background: As prevalence of multimorbidity and polypharmacy rise, healthcare systems must respond to these challenges. Data are needed from general practice on specific metrics of healthcare utilisation. This research aims to establish the rates of attendance to general practice and referral to hospital; and how age, multi-morbidity and polypharmacy affect them.Methods: This was a retrospective study of general practices in a university-affiliated education and research network, consisting of 72 practices. Records from a random sample of 100 patients aged 50 years and over who attended each participating practice in the previous 2 years were analysed. Through manual record searching, data were collected on patient demographics, number of chronic illnessesand medications, numbers of attendances to the general practitioner (GP), practice nurse, home visits and referrals to a hospital doctor. Attendance and referral rates were expressed per person-years for each demographic variable and the ratio of attendance to referral rate was also calculated.Results: Of the 72 practices invited to participate, 68 (94%) accepted, providing complete data on a total of 6603 patients’ records and 89,667 consultations with the GP or practice nurse; 50.1% of patients had been referred to hospital in the previous 2 years. The attendance rate to general practice was 4.94 per person per year and the referral rate to the hospital was 0.6 per person per year, giving a ratio of over eight attendances for every referral. Increasing age, number of chronic illnesses and number of medications were associted with increased attendance rates to the GP and practice nurse and home visits but did not significantly increase the ratio of attendance to referral rate.Discussion: As age, morbidity and number of medications rise, so too do all types of consultations in general practice. However, the rate of referral remains relatively stable. General practice must be supported to provide person-centred care to an ageing population with rising rates of multi-morbidity and polypharmacy.